A Preliminary study on social media use in government agencies - Mohd Nadzir, Maslinda; Othman, Nafishah; Kamaruddin, Siti Sakira (American Scientific Publishers, 2017)
Various countries are strategically using social media sites to reach their citizens in order to enhance government-citizens relationship in terms of communication, collaboration and engagement. In Asia, only a few countries are taking the effort to fully utilize social media to increase citizens’ engagement. The Malaysian government has established new policy for social media usage in public sector however there were no study on the extent of the impact. This paper investigates the Malaysian e-government Facebook page by carrying out a quantitative content analysis on page posts and public comments to obtain preliminary insights regarding the extent of social media usage to encourage public engagement.The purpose of this study is to identify the type of content and whether the provided content encourages the citizens to participate. The analysis result revealed that most government agencies posts information related to public awareness in their Facebook page while most public comments are targeted to the posts regarding promotions. The findings of this study can be used as a guideline for the government agencies to provide more relevant contents to improve their public engagement strategy.